PENGARUH CAR, FDR,BOPO TERHADAP ROA DENGAN NPF SEBAGAI VARIABEL INTERVENING PADA BTPN SYARIAH 2015-2019 - Mirawati Mirawati; Rahmad Ade Putra; Meli Diana Fitri (MABIS: Jurnal Manajemen Bisnis Syariah, 2021)
Profit (ROA) is the main goal in the company. The greater that affects profits, of course, makes this profit change every year. The purpose of this study is to provide an overview to see the magnitude of the influence of CAR, FDR, BOPO on ROA with NPF as an intervening. The method used is a quantitative method with a descriptive approach. The conclusion that can be drawn is that CAR has a negative and significant effect on ROA, FDR statistically has a negative and insignificant effect on profitability (ROA), BOPO has a negative and significant effect on ROA, NPF statistically has a negative and insignificant effect on profitability (ROA). CAR, FDR, BOPO, and, NPF have a joint effect on ROA, CAR has a significant positive effect on NPF, FDR has a significant negative effect on NPF, BOPO has a significant negative effect on NPF, NPF cannot significantly mediate CAR on ROA, NPF cannot mediate significant CAR on ROA, NPF can significantly mediate BOPO on ROA.